Modelling methodology of temperature and energy consumption in food plant: Application to puff pastry. (July 2020) - Duret, Steven; Hamon, Erwann; Hoang, Hong-Minh; Stahl, Valérie; Derens-Bertheau, Evelyne; Delahaye, Anthony; Laguerre, Onrawee
Highlights: This study focuses on a food plant of puff pastry. A thermal and energy modelling approach was developed. Industrial own-check data were mainly used. The thermostat setting temperature can be raised in this application. Abstract: This study focuses on the experimental and numerical characterization of the food temperature and energy consumption of cold facilities in a food processing plant. An event based framework was used to model the main components of the production line (kneader, conveyor, cooling spiral and cold room). Plant self-control data obtained by measurement in plant were used to inform and validate the model. Different scenarios were tested to evaluate the impact of modified operating conditions (thermostat setting temperature and duration) and refrigerating equipment outages on energy consumption and food temperatures. Up to 18% of energy savings could be achieved by increasing thermostat setting temperature of the process room and the storage room with a limited impact on the product temperature. This methodology can help manufacturers in decision making to optimize operating conditions and reduce energy consumption with a limited impact on food waste and safety.